Study on co-liquefaction of Spirulina and Spartina alterniflora in ethanol-water co-solvent for bio-oil. (15th July 2018) - Feng, Huan; Zhang, Bo; He, Zhixia; Wang, Shuang; Salih, Osman; Wang, Qian
Abstract: Spartina alterniflora of Lignocellulosic biomass is an invasive plant that rapidly grows in China which threatens the local ecological balance. The possibility of co-liquefaction (CL) of Spartina alterniflora with a low-lipid containing microalgae Spirulina in ethanol-water co-solvent (EWCS) for bio-oil production was investigated. The results show that bio-oil productivity was increased to 45.63 wt% with a higher heating value (HHV) of 34 MJ/kg, just because of the positive synergistic effect from CL process. In addition, the synergistic effect of bio-oil production has different performance at different temperatures, ethanol volume fraction or raw material blending ratio. Bio-oils were analyzed by GC-MS and FT-IR, which showed CL of mixed raw material resulted in a significant increase of hexadecanoic acid ethyl ester compared to liquefaction of pure Spirulina or Spartina alterniflora, indicated a good quality of bio-oil produced. Highlights: CL of Spirulina & Spartina alterniflora was studied in EWCS for the first time. Positive synergistic effect was found in CL process. Significantly increase the output of esters in bio-oil was found in CL. More violent polymerization and Maillard were found in CL. Energy recovery rate has been significantly improved in CL.